Enhancement of HIV-1 infection and intestinal CD4+ T cell depletion ex vivo by gut microbes altered during chronic HIV-1 infection. Issue 1 (December 2016) - Dillon, Stephanie; Lee, Eric; Donovan, Andrew; Guo, Kejun; Harper, Michael; Frank, Daniel; McCarter, Martin; Santiago, Mario; Wilson, Cara
Abstract Background Early HIV-1 infection is characterized by high levels of HIV-1 replication and substantial CD4 T cell depletion in the intestinal mucosa, intestinal epithelial barrier breakdown, and microbial translocation. HIV-1-induced disruption of intestinal homeostasis has also been associated with changes in the intestinal microbiome that are linked to mucosal and systemic immune activation. In this study, we investigated the impact of representative bacterial species that were altered in the colonic mucosa of viremic HIV-1 infected individuals (HIV-altered mucosal bacteria; HAMB) on intestinal CD4 T cell function, infection by HIV-1, and survival in vitro. Lamina propria (LP) mononuclear cells were infected with CCR5-tropic HIV-1BaL or mock infected, exposed to high (3 gram-negative) or low (2 gram-positive) abundance HAMB or control gram-negativeEscherichia coli and levels of productive HIV-1 infection and CD4 T cell depletion assessed. HAMB-associated changes in LP CD4 T cell activation, proliferation and HIV-1 co-receptor expression were also evaluated. Results The majority of HAMB increased HIV-1 infection and depletion of LP CD4 T cells, but gram-negative HAMB enhanced CD4 T cell infection to a greater degree than gram-positive HAMB. Most gram-negative HAMB enhanced T cell infection to levels similar to that induced by gram-negativeE. coli despite lower induction of T cell activation and proliferation by HAMB. Both gram-negative HAMB andE. coli significantly increased expression of HIV-1 co-receptor CCR5 on LP CD4 T cells. Lipopolysaccharide, a gram-negative bacteria cell wall component, up-regulated CCR5 expression on LP CD4 T cells whereas gram-positive cell wall lipoteichoic acid did not. Upregulation of CCR5 by gram-negative HAMB was largely abrogated in CD4 T cell-enriched cultures suggesting an indirect mode of stimulation. Conclusions Gram-negative commensal bacteria that are altered in abundance in the colonic mucosa of HIV-1 infected individuals have the capacity to enhance CCR5-tropic HIV-1 productive infection and depletion of LP CD4 T cells in vitro. Enhanced infection appears to be primarily mediated indirectly through increased expression of CCR5 on LP CD4 T cells without concomitant large scale T cell activation. This represents a novel mechanism potentially linking intestinal dysbiosis to HIV-1 mucosal pathogenesis.